2015
DOI: 10.1093/jxb/erv404
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of transcriptomic, biochemical, and physiological responses to elevated ozone identifies species-specific mechanisms of resilience in legume crops

Abstract: HighlightPhotosynthesis and leaf longevity were unaffected by growth in elevated [O3] in pea. Resilience to elevated [O3] was supported by transcriptional and biochemical metabolism associated with detoxification and antioxidant metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 82 publications
(94 reference statements)
5
35
0
Order By: Relevance
“…Similar effects of O 3 stress on central metabolism have been reported previously: changes in the activity and expression of genes and pathways involved in detoxification and redox balance (e.g. the aldehyde dehydrogenase ALDH, chloroplastic superoxide dismutase activity, and NADH regeneration) were linked to stomatal closure, decreased photosynthetic activity, and increased mitochondrial respiration Yendrek et al, 2015). However, when herbivory was applied as a second stress, all these initial effects of O 3 stress were reversed, resulting in decreased levels of sugars and amino acids and a reconfiguration of gene expression, including down-regulation of the amino acid transporter AAP2, which promotes nitrogen accumulation in siliques and seed development in Arabidopsis (Hirner et al, 1998;Ortiz-Lopez et al, 2000).…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 82%
“…Similar effects of O 3 stress on central metabolism have been reported previously: changes in the activity and expression of genes and pathways involved in detoxification and redox balance (e.g. the aldehyde dehydrogenase ALDH, chloroplastic superoxide dismutase activity, and NADH regeneration) were linked to stomatal closure, decreased photosynthetic activity, and increased mitochondrial respiration Yendrek et al, 2015). However, when herbivory was applied as a second stress, all these initial effects of O 3 stress were reversed, resulting in decreased levels of sugars and amino acids and a reconfiguration of gene expression, including down-regulation of the amino acid transporter AAP2, which promotes nitrogen accumulation in siliques and seed development in Arabidopsis (Hirner et al, 1998;Ortiz-Lopez et al, 2000).…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 82%
“…Thus, balancing the interplay of redox homeostasis and PCD pathways is essential for the breeding of ozone‐tolerant crop plants. As a first line of defence against ozone stress, high levels of apoplastic antioxidants such as ascorbate may mitigate ROS formation, a concept that has been confirmed in crop plants such as wheat (Feng, Pang et al., ) and legumes (Yendrek, Koester, & Ainsworth, ). Breeding for high levels of antioxidants is also assumed to cause synergies with other types of abiotic stress tolerance, including for drought and heat, both of which are associated with oxidative stress (Gill & Tuteja, ).…”
Section: Resultsmentioning
confidence: 94%
“…; Yendrek et al . ). A recent study in strawberry ( Fragaria × ananassa ) investigating plant responses after treatment with different low, medium and high doses of CO (133–533 ppb), NO x and SO 2 (0.05–0.20 ppm) showed that prolonged exposure to the pollutants resulted in continuous ROS production in leaves, with a negative effect on stomatal closure and photosynthesis (Muneer et al .…”
Section: Plant Physiological and Molecular Responses To Combinations mentioning
confidence: 97%
“…In a recent study on different varieties of legume, Yendrek et al . () combined physiological screening with transcriptomic and metabolic analyses, showing that while O 3 reduced leaf growth and sugar content, it increased the expression of transcripts associated with cellular respiration and GR activity, thus simultaneously inducing higher levels of antioxidant metabolites such as GSH and ascorbic acid (Yendrek et al . ).…”
Section: Plant Physiological and Molecular Responses To Combinations mentioning
confidence: 99%